The Dispossession of the Northern Ojibwa and Cree: The Case of the Chapleau Game Preserve - Calverley, David (Ontario History)

(untitled) (The Ontario Historical Society, 2009)
Park and game preserve creation, while usually lauded as a step towards the conservation of nature and wildlife, served to dispossess First Nations of traditional harvesting territories. In 1925 the Chapleau Game Preserve caused the removal of two First Nations communities: the New Brunswick House Reserve and the Michipicoten Ojibwa. Despite protests and efforts to reclaim this land, both communities were removed from the region. Historians have largely ignored this element of Canada’s wildlife conservation history.